Comparative analysis of the MYB gene family in seven Ipomoea species - Si, Zengzhi; Wang, Lianjun; Ji, Zhixin; Zhao, Mingming; Zhang, Kai; Qiao, Yake (Frontiers in Plant Science, 2023)
The MYB transcription factors regulate plant growth, development, and defense responses. However, information about the MYB gene family in Ipomoea species is rare. Herein, we performed a comprehensive genome-wide comparative analysis of this gene family among seven Ipomoea species, sweet potato (I. batatas), I. trifida, I. triloba, I. nil, I. purpurea, I. cairica, and I. aquatic, and identified 296, 430, 411, 291, 226, 281, and 277 MYB genes, respectively. The identified MYB genes were classified into five types: 1R-MYB (MYB-related), 2R-MYB (R2R3-MYB), 3R-MYB (R1R2R3-MYB), 4R-MYB, and 5R-MYB, and the MYB-related or R2R3-MYB type was the most abundant MYB genes in the seven species. The Ipomoea MYB genes were classed into distinct subgroups based on the phylogenetic topology and the classification of the MYB superfamily in Arabidopsis. Analysis of gene structure and protein motifs revealed that members within the same phylogenetic group presented similar exon/intron and motif organization. The identified MYB genes were unevenly mapped on the chromosomes of each Ipomoea species. Duplication analysis indicated that segmental and tandem duplications contribute to expanding the Ipomoea MYB genes. Non-synonymous substitution (Ka) to synonymous substitution (Ks) [Ka/Ks] analysis showed that the duplicated Ipomoea MYB genes are mainly under purifying selection. Numerous cis-regulatory elements related to stress responses were detected in the MYB promoters. Six sweet potato transcriptome datasets referring to abiotic and biotic stresses were analyzed, and MYB different expression genes’ (DEGs’) responses to stress treatments were detected. Moreover, 10 sweet potato MYB DEGs were selected for qRT-PCR analysis. The results revealed that four responded to biotic stress (stem nematodes and Ceratocystis fimbriata pathogen infection) and six responded to the biotic stress (cold, drought, and salt). The results may provide new insights into the evolution of MYB genes in the Ipomoea genome and contribute to the future molecular breeding of sweet potatoes.